Early Warning System Kerentanan Keuangan Asuransi Syariah di Indonesia - Adi Kurnia Hidayat; Firdaus, Achmad; -, Indra (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This study aims as a first step in determining the financial health of the company using the Early Warning System (EWS) financial ratios and early corporate bankruptcy. This research aims to analyze the Altman Z-Score and Fulmer Model models which will be used as an Early Warning System (EWS) for sharia insurance vulnerabilities in Indonesia. The Altman Z-Score and Fulmer Model methods use data obtained from financial reports and processed as a measure of financial health. The ratio that influences the financial vulnerability of sharia insurance in Indonesia using the Altman method which has been modified using PCA is the ratio of retained earnings/total assets (X2) and income before tax/total assets (X3). Meanwhile, the influential ratios from the Fulmer method modified using PCA found 3 ratios that influenced the financial vulnerability of sharia insurance in Indonesia, namely Retained Earning/Total Assets (V1), EBT/Equity (V3) and Cash Flow/Total Debt (V4).